Two new species of myxosporean parasites (Myxosporea: Bivalvulida) from gall bladders of Macruronus magellanicus Lönnberg, 1907 (Teleostei: Merlucciidae) - Kalavati, Chaganti; Mackenzie, Ken; Collins, Catherine; Hemmingsen, Willy; Brickle, Paul (Zootaxa, 2013)
Two new species of myxosporeans are described from the gall bladders of hoki, Macruronus magellanicus Lönnberg, 1907, caught in the Southeast Pacific off Chile and in the Southwest Atlantic off the Falkland Islands. Pseudalataspora kovalevae n. sp. is described morphologically and genetically. Of the 12 species of Pseudalataspora previously described from the gall bladders of marine fish, P. kovalevae is most similar in morphology to P. umbraculiformis Gaevskaya and Kovaleva, 1984. The 18S rRNA gene sequence from P. kovalevae is the first for a member of the genus Pseudalataspora. Based on currently available myxosporean 18S rRNA gene sequence data, P. kovalevae shares greatest sequence identity with species of the genus Ceratomyxa (C. anko and C. pantherini). Palliatus magellanicus n. sp. is described morpholog-ically only; it differs considerably in morphology, host species and locality from the five other Palliatus species described from marine fishes. A third species from the gall bladder is also described morphologically and genetically. On the basis of its morphology it is tentatively identified as Myxidium baueri Kovaleva and Gaevskaya, 1982, for which M. magellani-cus is a new host record. Molecular analysis indicates that, of those species for which data are available, M. baueri is most closely related to Myxidium coryphaenoideum Noble, 1966 based on 18S rRNA gene sequence data, though support for a phylogenetic grouping is lo